Pengetahuan Perempuan Indonesia Tentang HIV/AIDS - Lilik Iswanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2011)
HIV/AIDS is a serious health problem in the world, including in Indonesia. It has a huge impact in economic, social and political aspects. There fore research regarding the knowledge of HIV/AIDS become important. This paper explores women’s knowledge of HIV/AIDS in Indonesua using secondary data from Indonesia Demographic and Health Survey (IDHS) 2007. In measuring the knowledge indicator used such as have you ever heard about HIV/AIDS, knowledge of the transmission abd HIV/AIDS prevention. Statistic descriptive, composit and binary logistic were using to answer the research problem. The result shows that women’s knowledge in HIV/AIDS is fairly good. The main factor which influence women’s knowledge of HIV/AIDS is their level of education along with their spouse. Women who have finished their education in senior high has twice better knowledge on HIV/AIDS compared to those who did not finish.